Is Medium-term Exposure to Ambient Air Pollution a Risk Factor for Parkinson’s Disease? - Babak Jahanshahi; Duncan McVicar; Neil Rowland (International Journal of Population Data Science, 2024)
Objectives This study used Census data from Northern Ireland linked to administrative data on prescriptions between 2010 and 2016, to examine the association between ambient air pollution exposure and the risk of Parkinson’s Disease (PD) onset. It contributes to this literature by providing new evidence in a comparatively low pollution context, using rich and nationally representative cohort data with comprehensive information on Parkinson’s Disease medications dispensed over an extended period.